CONTEMPORARY RELIGIOUS EDUCATION MODEL ON THE CHALLENGE OF INDONESIAN MULTICULTURALISM (State Islamic University (UIN) of Sunan Ampel Surabaya, 2016)
This paper discusses the issue of religious education in relation to the challenge of religious multiculturalism in Indonesia. The focus of this paper is to find out the kind of religious education that is compatible with the challenge of religious multiculturalism. By employing the concept of religious multiculturalism and theory of religious education, this paper argues that to face the challenge of religious multiculturalism it is necessary to change the model of religious education from within, at and beyond the wall. Religious education “in” the wall contributes to shape an exclusive model of religiosity; while religious education “at” and “beyond” the wall contributes to shape an inclusive multiculturalistic model of religiosity. The last two models are applicable in Indonesia in order to face the challenge of multiculturalism, because both of them help students to accept, respect, and value religious differences. Religious education should show that the common enemy of religion is not people of different faiths, but poverty, corruption, violence, ignorance, and the like, and they have to stand together to fight against these true enemies.